Pengaruh Marketing Mix terhadap Keputusan Pembelian Konsumen pada Queen Bakery di Kabupaten Bandung Barat - Aldy Santo Hegiarto; Apriyani Regina Putri (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This study aims to determine the influence of marketing mix measured through the dimensions of product, price, place, promotion, people, process, packaging, and physical evidence on the purchasing decisions of Queen Bakery company consumers. This research uses quantitative research methods with quantitative descriptive analysis methods. Sampling using purposive sampling technique with a sample of 100 respondents using the Slovin formula. The data analysis technique used to answer the hypothesis is multiple linear regression analysis using SPSS for windows version 27. Based on the results of data analysis, it shows that partially only the variables Product, Price, Place, Process have a positive and significant effect on the purchasing decisions of Queen Bakery consumers in West Bandung District. While Promotion, People, Packaging, Physical Evidence and Marketing Mix 8P partially does not affect the purchasing decisions of Queen Bakery consumers in West Bandung District. The result of the F test count of 22.930 with a significance level of 0.000 shows that Marketing Mix 8P simultaneously or simultaneously influence the purchasing decisions of Queen Bakery consumers in West Bandung District.